THE RELATIONSHIP BETWEEN BANKS AND COMPANIES: THE LITERATURE REVIEW - Paoloni, Niccolo (Poslovna ekonomija, 2018)
This paper aims at reviewing the national and international literature on the lending relationship between banks and companies in Italy in light of the regulatory changes introduced by the Basel Committee in its various versions, in order to understand the “state of the art” and if and to what extent these issues have been dealt with in the various studies so far – how did bank-company relationships change after the 2007-2010 economic crisis? What are the effects of the Community regulation on the financing system in Italy? This article is based on a revision of the literature on the changed bank-company relationship in the post-economic crisis years. To this purpose, a bibliographic research was conducted on Scopus, using a series of selected keywords. The publications identified were analyzed and classified, in an attempt to determine the main topics and the results obtained thanks to the research and analysis carried out to-date. This work contributes to the literature on the subject of the bank-company relationship and proposes a new perspective applied to an issue of great relevance in a period of economic recovery when financial support to companies is of crucial importance. Our revision of the literature highlights that this issue is not deeply studied as far as search for and availability of external sources of financing are concerned, which gives us the possibility to identify new questions and find new solutions to the problems connected with the sustainability of both public and private investments.